Transparency phenomena of flat-rice noodles (kuew teow) at drying at soaking variation - Ismail, Muhammad Heikal; Law, Chung Lim; Hii, Ching Lik (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
This paper presents a transparency phenomenon that occurred in hot air and heat pump dried flat-rice noodles, which is explained by the higher colour changes, glassy puffing microstructures, and lower fat content in comparison to the freeze dried flat-rice noodles. Hot air drying and heat pump drying recorded the colour changes at an average of 43.87 ± 1.5 twice than colour change caused by freeze drying at 19.33 ± 1.12 to verify the transparency caused by employing high temperature to eventually increase the sample lightness. However, the microstructures study suggested that freeze drying produced distinct pores ranging from 2.05 μm to 27.68 μm whereby hot air drying and heat pump drying merely produced glossy transparent texture. Indeed, the pores disclose the fat content recorded by freeze drying in flat-rice noodles at 5.62% ± 0.2 twice than the fat content recorded by hot air and heat pump drying at 2.48% ± 0.49. Therefore, by learning the transparency phenomenon in hot air and heat pump dried noodles approves that freeze drying eventually preserves the quality attributes of flat-rice noodles as closest to the fresh flat-rice noodles in terms of colour, microstructures, and fat content.